2016
DOI: 10.1111/ajt.13803
|View full text |Cite
|
Sign up to set email alerts
|

High Intrapatient Variability of Tacrolimus Concentrations Predicts Accelerated Progression of Chronic Histologic Lesions in Renal Recipients

Abstract: High intrapatient variability (IPV) of tacrolimus concentrations is increasingly recognized as a predictor of poor outcome in solid organ recipients. How it relates to evolution of histology has not been explored. We analyzed tacrolimus IPV using the coefficient of variability (CV) from months 6-12 after transplantation in a cohort of 220 renal recipients for whom paired protocol biopsies at 3 mo and 2 years were available. Recipients in the highest CV tertile had an increased risk of moderate to severe fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(192 citation statements)
references
References 27 publications
10
176
4
2
Order By: Relevance
“…Like the studies described above, race was not reported or accounted for in analyses. 15 Finally, Whelan et al, recently demonstrated that high tacrolimus intrapatient variability significantly increased the risk of acute rejection, reduced estimated glomerular filtration rates (GFRs) and increased graft loss in 366 renal transplant recipients receiving a low-exposure tacrolimus regimen. However, only 18 patients were nonwhite.…”
Section: Discussionmentioning
confidence: 99%
“…Like the studies described above, race was not reported or accounted for in analyses. 15 Finally, Whelan et al, recently demonstrated that high tacrolimus intrapatient variability significantly increased the risk of acute rejection, reduced estimated glomerular filtration rates (GFRs) and increased graft loss in 366 renal transplant recipients receiving a low-exposure tacrolimus regimen. However, only 18 patients were nonwhite.…”
Section: Discussionmentioning
confidence: 99%
“…111 In addition, increased IPV of tacrolimus has been associated with the development of de novo DSAs, 112 and faster progression of interstitial fibrosis. 113 In the context of liver transplantation, the clinical impact of tacrolimus variability has seldom been studied. Patients with biopsy-proven TCMR showed increased standard deviations of tacrolimus trough concentrations according to 1 report.…”
Section: Strategies For Managing Nonadherencementioning
confidence: 99%
“…Furthermore, in a recent study of 220 kidney transplant recipients, higher tacrolimus intrapatient variability predicted accelerated progression of chronic histologic lesions before onset of renal dysfunction. 73 The lower-dose tacrolimus plus MMF and steroid regimen used in the Symphony study is the most commonly used in clinical practice. In a subanalysis of data from this study, intrapatient variability of tacrolimus exposure of~28% was apparent with this regimen in the first 12 months.…”
Section: Variability Of Immunosuppressive Exposure In Kidney Transplamentioning
confidence: 99%